Human capital effects in the job search process for new labor market entrants: A double-edged sword? - NG, Jomel Wei Xuan (Institutional Knowledge at Singapore Management University, 2023)
Although traditional research on human capital shows that it enhances employment success, its role in the job search process is unclear. To explain its weak effects in previous studies, this study draws on goal system theory to propose that human capital may act as a double-edged sword: On one hand it facilitates the ease of gaining employment, on the other hand it may compromise the frequency of job search behaviors. We conducted a bi-weekly repeated survey study on new labor market entrants and measured human capital using academic achievement scores. Results confirmed that human capital, though instrumental for proximal job search success, interferes with self-regulatory behaviors in job search. That is, human capital negatively predicted withinperson job search intensity, and negatively moderated the within-person relationship between employment efficacy and job search intensity. On the positive side, human capital positively predicted within-person number of interview invitations. Overall, these results provide a more nuanced picture of the role of human capital in the job search process.